2022
DOI: 10.5114/hpc.2022.113599
|View full text |Cite
|
Sign up to set email alerts
|

Importance of ticks in the transmission of selected bacterial pathogens of human diseases

Abstract: Teodorowicz, Marcin Weiner. This is an Open Access journal, all articles are distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International (CC BY-NC-SA 4.0) License (http://creativecommons.org/licenses/by-ncsa/4.0/), allowing third parties to copy and redistribute the material in any medium or format and to remix, transform, and build upon the material, provided the original work is properly cited and states its license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The best-known co-infection in ticks and humans is that caused by the pathogens of current interest, A. phagocytophilum and B. burgdorferi s.l. ( 21 , 35 ). Previous studies in Poland rarely reported the presence of this co-infection in I. ricinus ticks infesting domestic animals.…”
Section: Discussionmentioning
confidence: 99%
“…The best-known co-infection in ticks and humans is that caused by the pathogens of current interest, A. phagocytophilum and B. burgdorferi s.l. ( 21 , 35 ). Previous studies in Poland rarely reported the presence of this co-infection in I. ricinus ticks infesting domestic animals.…”
Section: Discussionmentioning
confidence: 99%